Singleton Pregnancy Outcomes after In Vitro Fertilization with Fresh or Frozen-Thawed Embryo Transfer and Incidence of Placenta Praevia - Korosec, Sara (Hindawi Publishing Corporation, 2014)
The aim of the study was to compare the single pregnancy and neonate outcome after fresh and frozen-thawed embryo transfer in the in vitro fertilization programme (IVF). The study focused on clinical and laboratory factors affecting the abnormal placentation, especially placenta praevia, in patients conceiving in the IVF programme. The results confirm that neonates born after frozen-thawed embryo transfer had significantly higher mean birth weight than after fresh embryo transfer (ET). Moreover, the birth weight distribution in singletons was found to shift towards “large for gestation” (LGA) after frozen-thawed ET. On the other hand, the pregnancies after fresh ET were characterized by a higher incidence of placenta praevia and 3rd trimester bleeding. Placenta praevia was more common in IVF patients with fresh ET in a stimulated cycle than in patients with ET in a spontaneous cycle. It occurred more frequently in patients with transfer of 2 embryos. From this point of view, single ET and ET in a spontaneous cycle should be encouraged in good prognosis patients in the future with more than two good quality embryos developed. An important issue arose of how the ovarian hormonal stimulation relates to abnormal placentation and if the serum hormone levels interfere with in the IVF treatment results.